2017
DOI: 10.1002/biot.201600574
|View full text |Cite
|
Sign up to set email alerts
|

Genetic engineering of the branched fatty acid metabolic pathway of Bacillus subtilis for the overproduction of surfactin C14 isoform

Abstract: Surfactin, a lipopeptide produced by Bacillus subtilis, is one of the most powerful biosurfactants known. This molecule consists of a cyclic heptapeptide linked to a β-hydroxy fatty acid chain. The isomery and the length of the fatty acid (FA) chain are responsible for the surfactin's activities. In this study, the gene codY, which encode for the global transcriptional regulator and the gene lpdV, located in the bkd operon (lpdV, bkdAA, bkdAB and bkdB genes), which is responsible for the last step of the branc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 39 publications
4
47
0
Order By: Relevance
“…Compared with the NRPS-catalyzed synthesis of the peptide structure, the biosynthesis of the fatty acyl structure of the surfactin molecule still needs further research. The fatty acid chain length of surfactin is generally C 13 –C 15 , whereby C 14 and C 15 are usually predominant (60–80%) [34]. The length and isomerism of the FA chain were known to have an impact on the physicochemical properties and biological activity [86].…”
Section: Structural Modification Of Surfactinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the NRPS-catalyzed synthesis of the peptide structure, the biosynthesis of the fatty acyl structure of the surfactin molecule still needs further research. The fatty acid chain length of surfactin is generally C 13 –C 15 , whereby C 14 and C 15 are usually predominant (60–80%) [34]. The length and isomerism of the FA chain were known to have an impact on the physicochemical properties and biological activity [86].…”
Section: Structural Modification Of Surfactinsmentioning
confidence: 99%
“…The relative proportions of C 13 and C 14 in the control strain were 39.7% and 21.2%, respectively, which changed to 26.5% and 40.6% after knocking out codY . Later, Coutte et al further studied the branched-chain amino acid metabolic pathway and found that the proportion of surfactin with linear C 14 was increased 2.5 times after knocking out the lpdV gene responsible for the final degradation of branched-chain amino acids [34].…”
Section: Structural Modification Of Surfactinsmentioning
confidence: 99%
“…Others achieved srfA overexpression by upregulating the quorum sensing system ComQXPA [11, 1315] or downregulating the negative factors [13, 14, 16–19]. Dhali et al [20]. enhanced the production to 1556 ± 123 mg of surfactin per g dry weight of cell biomass by knocking out the global regulation factor codY , which had negative effects on srfA expression.…”
Section: Introductionmentioning
confidence: 99%
“…Surfactin is a lipopeptide biosurfactant composed of a cyclic ring of amino acids linked to hydroxylic fatty acids by a lactone bond [ 41 , 42 ]. The cyclic peptide part contains two hydrophilic residues of Glu and Asp acid because of free groups of COO − at a pH above pK a = 5.8 [ 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%